Alzheimer's disease amyloidogenesis is linked to altered lower urinary tract physiology. Issue 6 (17th May 2022) - Hardy, Cara C.; Ramasamy, Ramalakshmi; Rosenberg, Dawn A.; Kuchel, George A.; Yan, Riqiang; Hu, Xiangyou; Smith, Phillip P.
Abstract: Aims: While most Alzheimer's disease (AD) research emphasizes cognitive and behavioral abnormalities, lower urinary tract symptoms (LUTS) are observed in a third of AD patients, contributing to morbidity, poor quality of life, and need for institutionalization. Alzheimer's disease‐associated urinary dysfunction (ADUD) has been assumed to be due to cognitive decline alone. While mouse studies have suggested that bladder innervation and voiding behavior may be altered in AD models, technical challenges precluded voiding reflex assessments. This study seeks to establish a mouse model of ADUD, and it seeks to characterize the noncognitive sequelae involved in AD‐pathology associated alterations in the voiding reflex. Methods: Having developed techniques permitting the assessment of bladder volume, pressure, and flow in mice, we now provide evidence of alterations in involuntary bladder control and increased response heterogeneity in a transgenic amyloidosis mouse model of AD using cystometry and tissue pharmacomyography. Tg‐APP/PS1DE9 (PA) mice and their wild‐type (WT) littermates ( n = 6–8 per group) were used before plaque onset in the PA mice (4–6 months) and after plaque accumulation in the PA mice (8–10 months) in comparison to their WT control littermates. Results: Novel findings include data suggestive of sphincteric discoordination, with pharmacological evidence of altered adrenergic mechanisms. Conclusions: Together, these data highlight the importance of addressing noncognitive sequelae of AD and offer novel translational insights into the debilitating impact of AD on LUTS and incontinence.